PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBASIS LESSON STUDY UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN AKTIVITAS MAHASISWA PENDIDIKAN BIOLOGI UNIVERSITAS NEGERI MALANG PADA MATA KULIAH PENGEMBANGAN KURIKULUM - Prasmala, Erfitra Rezqi (JEMS Jurnal Edukasi Matematika dan Sains, 2015)
The aim of research to improve the activity and student understanding of conceptsCurriculum Development at S1 Department of Biology, State University ofMalang by applying the model of Problem Based Learning (PBL) based Lessonstudy. Type of research is action Action Research (PTK) based Lesson study. PBLmodel application can increase the activity and student understanding of concepts.Based on the discussion of the suggestions in this study was not able to be doneindependently entirely by students as well as the need for time management aseffectively as possible.